DAMPAK NEGATIF INVASI MILITER JEPANG PADA ZAMAN SHOUWA DALAM MANGA MADOMOWAZERU BATAFURAI KARYA OGURA AKANE - Dwi Udiyani, Ida Ayu (Humanis, 2014)
History are often used as setting in literature work like comics, one of them is Madomowazeru Batafurai. The comic reflected the negative impact of Japanese invasion on the Shouwa era againts Japanese society. By using the theory of postcolonialism, the comic is analyzed from the point of view of history to see the Shouwa era’s history reflection and the negative impact of Japanese invasion. According to the result of the analysis the Shouwa era’s history reflection in the comic are the negative impact of Japanese invasion which reflected in Madomowazeru Batafurai comic are great hunger in Japan, coup in the capital, China-Japan War, Pacific War, and Sea Battle Philippine. The social impact of Japanese invasion are sending Japanese young men to the war battlefield, limited goods and the lack of foods, decreasing of jobs, the peoples are lost their homes, and many victims. The psychology impact of Japanese invasion are worries the family of the young men at war, sadness the family left war, depressed Japanese young men, and deep sorrow for the death of the family in the war.
Keywords: Shouwa era, Japanese invasion, negative impact.